I 1eff = I 1 2 ×X+ I 0 2 ×(1−X) MathType@MTEF@5@5@+= feaagKart1ev2aqatCvAUfeBSjuyZL2yd9gzLbvyNv2CaerbbjxAHX garuavP1wzZbItLDhis9wBH5garmWu51MyVXgaruWqVvNCPvMCG4uz 3bqee0evGueE0jxyaibaieYdi9WrpeeC0lXdi9qqqj=hEeeu0lXdbb a9frFj0xb9Lqpepeea0xd9s8qiYRWxGi6xij=hbba9q8aq0=yq=He9 q8qiLsFr0=vr0=vr0db8meaabaGacmGadiWaaiWabaabaiaafaaake aacaWGjbWaaSbaaSqaaiaaigdacaWGLbGaamOzaiaadAgaaeqaaOGa eyypa0ZaaOaaaeaacaWGjbWaa0baaSqaaiaaigdaaeaacaaIYaaaaO Gaey41aqRaamiwaiabgUcaRiaadMeadaqhaaWcbaGaaGimaaqaaiaa ikdaaaGccqGHxdaTcaGGOaGaaGymaiabgkHiTiaadIfacaGGPaaale qaaaaa@4DEF@